Hiperrealitas pada Media Sosial Pengguna Instagram di Kalangan Mahasiswa - Fadil Nurmansyah (Ad-Dariyah: Jurnal Dialektika, Sosial dan Budaya, 2021)
Currently Instagram social media is a need that is highly prioritized by students. Even students have made Instagram a social reality. The research entitled "Hyperreality in Social Media of Instagram Users" has formulated the problem of how Instagram users behave and what impression they want to show their followers to the reality they create on their Instagram account. The purpose of this study was to determine the various forms of behavior & motivation of Indonesian students in using Instagram. This research is in the form of a qualitative descriptive study. The data sources used are primary and secondary data. Data were analyzed using literature review study method. The theoretical basis used is the theory of hyperreality proposed by Jean Baudrillard. Based on the data analysis that has been done, it can be concluded that Instagram users are emotionally tied to the reality they get in the world of Instagram.